Bio-ink properties of gelatin methacrylamide - Seow, Li Yuan (2016)
In 2012, Singapore had 456 patients on the kidney transplantation waiting list and the shortage of organ transplantation drives the need for new regeneration therapy. It is widely believed that high precision 3D Bioprinting will be a new technology to improve regeneration therapy. The key challenge of the 3D Bioprinting is subjected to the availability of appropriate printable and cell compatible materials as bio-ink. Gelatin methacrylamide (GelMA) is a hydrogel material that has excellent cell viability and cytocompatibility which can potentially be used as a bio-ink material. However, limited research have been done on the feasibility of using GelMA as a bio-ink material. The objective of this study is to investigate the feasibility of using GelMA as a printable bio-ink material. The feasibility in this study of bio-ink will only cover the printability. GelMA that used in this study was chemically modified from gelatin Type A and Type B and was carried out using different percentages of degree of substitution (% of DS) and different concentrations. This study involved rheology studies and 3D Bioprinting. Rheology studies covered flow behaviour of the GelMA solutions under various shear rates and various temperatures. Frequency sweep test was also conducted to study the viscoelasticity of GelMA. Results obtained from rheology studies showed GelMA are shear thinning materials and their viscosities are dependent on % of DS, concentration and temperature. 20% weight per volume (% w/v) GelMA 2.2 Type A and Type B were selected as the test materials for 3D Bioprinting. These two samples have higher storage modulus properties (G’>G”). From 3D Bioprinting, 20 % w/v GelMA 2.2 Type A shows better resolution and shape fidelity than Type B. In summary, GelMA is feasible to be used as a bio-ink material as it exhibits the component of printability such as shear thinning properties and higher storage modulus properties (G’>G”). Due to machine limitation, not all GelMA samples could be studied in this project. Future studies on GelMA could involve optimising other printing parameters to explore its printing possibility.